Dependence On Debt Financing To Cover The Budget Deficit: Implications For Fiscal Sustainability - Mira Miranda; Sugiyanto, Sugiyanto (Jurnal Multidisiplin Indonesia, 2025)
This research examines the dependence on debt financing to cover budget deficits and its implications for fiscal sustainability. Using secondary data analysis from government financial reports during the 2010-2023 period, this study finds that the increasing debt-to-GDP ratio has exceeded the limits established within the fiscal sustainability framework. The results indicate that dependency on debt has created pressure on interest payments that absorb a significant portion of the annual budget and reduce fiscal space for priority sector financing. This research concludes that fiscal policy reforms emphasizing enhanced domestic revenue, spending efficiency, and strategic debt management are necessary to ensure long-term fiscal sustainability.